Variational Methods for an Impulsive Fractional Differential Equations with Derivative Term - Yulin Zhao; Jiafa Xu; Haibo Chen (Mathematics, 2019)
This paper is devoted to studying the existence of solutions to a class of impulsive fractional differential equations with derivative dependence. The used technical approach is based on variational methods and iterative methods. In addition, an example is given to demonstrate the main results.